2000
DOI: 10.1016/s0735-1097(00)00525-8
|View full text |Cite
|
Sign up to set email alerts
|

End-diastolic wall thickness as a predictor of recovery of function in myocardial hibernation

Abstract: End-diastolic wall thickness is an important marker of myocardial viability in patients with suspected hibernation, and it can predict recovery of function similar to T1-201 scintigraphy. Importantly, a simple measurement of EDWT < or =0.6 cm virtually excludes the potential for recovery of function and is a valuable adjunct to DSE in the assessment of myocardial viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(27 citation statements)
references
References 35 publications
0
26
0
1
Order By: Relevance
“…Diastolic wall thickness is >6 mm by CMR 70 or 7 mm on trans-thoracic echocardiography, 65 though recent studies have demonstrated that thinning below these thresholds, in the absence of extensive scar, does not preclude recovery. 71 With inotropic stimulation, hibernating myocardium shows ‘contractile reserve’ or a ‘biphasic response’, with an improvement in contractile function on low-dose/effort stress prior to deteriorating at higher workloads.…”
Section: Taxonomy For Myocardial Segmentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Diastolic wall thickness is >6 mm by CMR 70 or 7 mm on trans-thoracic echocardiography, 65 though recent studies have demonstrated that thinning below these thresholds, in the absence of extensive scar, does not preclude recovery. 71 With inotropic stimulation, hibernating myocardium shows ‘contractile reserve’ or a ‘biphasic response’, with an improvement in contractile function on low-dose/effort stress prior to deteriorating at higher workloads.…”
Section: Taxonomy For Myocardial Segmentsmentioning
confidence: 97%
“…63,64 The time course of recovery of LV systolic function following revascularization is dependent upon the severity of myocardial change, with some studies suggesting that irreversible remodelling may occur with extended hibernation despite successful revascularization. 64,65 However, it is not known if delayed recovery may occur beyond study duration. 66 …”
Section: Taxonomy For Myocardial Segmentsmentioning
confidence: 99%
“…This approach uses a cut-off value of ≥ 5.5–6 mm in most studies to determine whether a segment is viable [14]. Echocardiography and CMR can be used to measure the EDWT with the advantage of CMR that provides accurate measurements of the entire LV wall.…”
Section: Imaging Techniques Employed For Viability Assessmentmentioning
confidence: 99%
“…Polar viability maps were constructed based using the same 20 segment model as above, and viability defined as wall thickness >6 mm without delayed gadolinium enhancement 14. In areas of borderline wall thickness the segment was judged to be scar if the transmural extent of gadolinium enhancement was >25% 15…”
Section: Cmrmentioning
confidence: 99%